The Middle-Income Trap: Definitions, Theories and Countries Concerned—A Literature Survey. Issue 4 (December 2016) - Glawe, Linda; Wagner, Helmut
Abstract The term middle-income trap (MIT) usually refers to countries that have experienced rapid growth and thus quickly reached middle-income status, but then failed to overcome that income range to further catch up to the developed countries. This paper surveys the MIT literature. It begins by laying out different approaches to defining the MIT and by presenting as well as classifying the most important empirical studies. After a short overview of the currently identified MIT countries, the article summarizes the main explanatory approaches, taking into account both the theoretical foundations and the empirically identified triggering factors.